Approaches to the Quantification of the Human Capital Efficiency in Enterprises - Kucharcikova, Alzbeta; Konusikova, Lubica; Tokarcikova, Emese (Communications - Scientific letters of the University of Zilina, 2016)
Human capital is one of the enterprise inputs. There are people who are the bearers of new knowledge, ideas, experiences and skills; they contribute to their own personal growth as well as to increasing the performance and competitiveness of the whole enterprise. Human capital management helps enterprises to achieve enterprise goals just by using the human capital efficiently. For the assessment of the results achieved and directing further development it is important to know how to measure the efficiency. The aim of the article is: based on the study of special and scientific foreign literature to identify and compare the different theoretical approaches to the measurement of the efficient use of human capital for possible implementation in enterprise practice.